Evaluation of the implementation of the sekolah penggerak curriculum using the context, input, process and product evaluation model in high schools - Anggarda Paramita Muji; Nurhizrah Gistituati; Alwen Bentri; Fris Okta Falma (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2021)
Learning evaluation is to find out how far the progress, development, and success of students after carrying out the learning process within the specified time period is, including the evaluation of the innovative learning curriculum, namely the sekolah penggerak curriculum. The purpose of this study is to describe the evaluation of the school curriculum using the Context, Input, Process and Product (CIPP) evaluation model. Qualitative research designed in the form of case study research. The research subjects were the principal, curriculum representative, and school supervisor. Determination of research subjects was carried out purposively. Data collection techniques using observation sheets and data analysis techniques used are descriptive statistics. Research findings using the Context, Input, Process and Product (CIPP) is seen from the Context, Input, Process and Product aspects that the implementation of the sekolah penggerak curriculum is in accordance with the learning objectives. The implementation of this curriculum innovation is expected to have an impact on the quality of learning outcomes, the quality of the main competencies, the quality of teachers, the acceleration of school digitization and the profile of Pancasila students.